Informed Design of a Gravity Science Experiment for the Future Geophysical Investigation of the Uranian Moons - Valerio Filice; Gael Cascioli; Sébastien Le Maistre; Rose-Marie Baland; Antony Trinh; Erwan Mazarico; Sander Goossens (The Planetary Science Journal)
The outer solar system beyond Saturn remains unexplored by dedicated orbital missions. With a launch window opening in 2029, the Uranus Orbiter and Probe (UOP) mission has been prioritized as a NASA Flagship mission for the next decade (2023–2032) to comprehensively study Uranus and its major moons—Miranda, Ariel, Umbriel, Titania, and Oberon. We define and apply novel mission design principles centered on scientific objectives to UOP's gravity science (GS) experiment. Using a combination of Bayesian and Precise Orbit Determination inversions, it is possible to determine mission requirements ensuring the achievement of scientific goals. Our methodology involves building measurement-to-interior parameter maps via extensive Markov Chain Monte Carlo simulations, linking geodetic measurements’ precisions to uncertainties in key interior parameters of the Uranian moons. We show how this mapping approach allows for the rapid evaluation of the ability of a GS experiment design to constrain interior parameters. We conduct a covariance analysis of two orbital tours, multiple measurement strategies, and inversion settings. The tested cases enable the satisfactory determination of Ariel's ice shell thickness (to about 16%), as well as its rock-to-ice mass ratio (≈28%). None of the solutions were able to constrain its ocean thickness. This reverse approach allows for the rapid and scientifically informed adjustment of mission design, thereby demonstrating its potential applicability to other planetary science experiments.